SOIL QUALITY CHANGES FOLLOWING FOREST CLEARANCE IN BENGKULU, SUMATRA - I P HANDAYANI (SEAMEO BIOTROP, 2004)
Intense destruction and degradation of tropical forests is recognized as one of the environmental threats and tragedies. These have increased the need to assess the effects of subsequent land-use following forest extraction on soil quality. Therefore, the objective of this study is to evaluate the impacts of land-use type on soil quality properties in Bengkulu Province, Sumatra. Soil samples were collected from adjacent sites including natural secondary forest, bare land, cultivated land and grassland. The results show that land-use following forest clearance lowered saturated hydraulic conductivity (85%), porosity (10.50%), soil water content at field capacity (34%),C organic (27%), N total (26%), inorganic N (37%), soil microbial biomass C (32%), mineralizable C (22%), and particulate organic matter (50%), but slightly increased water soluble organic C. Specific respiration activity rates increased about 14% in cultivated soils compared to natural forest soils, indicating greater C turnover per labile C pool in the form of soil microbial biomass, thus decreased biologically active soil organic matter. Forest conversion tends to reduce the C,ffg/Crer for all deforested sites. All of deforested areas relatively have infertile soil, with the worst case found in cultivated field. The C^g/Crd of cultivated fields was about 24% less than that of remnant forest (1.07). Grassland apparently maintains only slightly higher soil C levels than the bare land. On average, degradation index of soil following forest clearance was 35% with the highest deterioration occurred in the bare land (38%). Fallowing the fields by naturally growth ofÂ Imperata cylindricaÂ for about 15 yr in abandoned land after 3-5 years of cultivation did not improve the soil quality. Moreover, forest clearance has an impact on soil quality as resulted in the loss of a physically protected organic matter and reduction in some labile C pools, thus declined biological activity at disturbed ecosystems. Keywords: Degradation index / forest / Imperata cylindrica grassland / soil quality/ soil organic matter